The Effect of Animated Video Education on the Level of Knowledge and Attitude in Efforts to Prevent Appendicitis in Adolescents - Nasution, Nurromsyah; Satria, Orita; Samsidar, Samsidar; Zakiyah, Zakiyah (Institute Of Computer Science (IOCS), 2025)
Appendicitis or inflammation of the appendix is one of the emergency cases that many teenagers experience. Lack of knowledge and appropriate preventive attitudes are significant risk factors. The use of interesting educational media such as animated videos is believed to be able to increase adolescents' understanding of the importance of healthy living behaviors to prevent appendicitis. Research objectives To determine the effect of animated video education on the level of knowledge and attitudes in efforts to prevent appendicitis in adolescents at SMP Negeri 3 Meulaboh. Method This study used a quasi-experimental design with a one-group pretest-posttest and cross-sectional approach. The sample consisted of 277 students, who participated in animated video education on January 24, 25, and 31, 2025. Research results There is a significant influence between animated video education on increasing adolescents' knowledge and attitudes in efforts to prevent appendicitis with statistical test results p-value = 0.000 <? = 0.05). Conclusion: Education using animated video media is effective in increasing knowledge and forming positive attitudes in adolescents in preventing appendicitis.